Adoption Status Of Livestock Innovations And Factors Affecting Their Adoption In Bidar District Of Karnataka - Rathod, Prakashkumar; Hiremath, Siddalingaswamy; H.V., Manjunathachar (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
An ex-post facto and exploratory study was conducted to assess the adoption status of livestock innovations and factors affecting their adoption in Bidar District of Karnataka. Among thirteen innovations studied, pregnancy diagnosis and vaccination against disease were the most adopted innovations while compost making/biogas and enrichment of roughages were the poorly adopted innovations. The study revealed that majority of dairy farmers belongs to medium level of innovativeness followed by high and low level of innovativeness. The study concluded that, there is a need to assess the technological gaps, actual adoption of technologies and factors affecting their adoption and diffusion at field conditions. Appropriate strategies must be developed by livestock agencies to have better impact and popularization of livestock technologies.